2021
DOI: 10.7759/cureus.13291
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Alkali Syndrome: Historical Review, Pathophysiology and Post-Modern Update

Abstract: Milk-alkali syndrome or calcium-alkali syndrome (CAS) is the triad of hypercalcemia, metabolic alkalosis and renal impairment. It is often related to ingestion of high amounts of calcium carbonate, which was used historically for the treatment of peptic ulcer disease. The incidence of the syndrome decreased dramatically after the introduction of newer peptic ulcer medications such as proton pump inhibitors and histamine blocking agents. However, a resurgence was seen in the late 1980s with the wide use of over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Other differential diagnoses of renal failure and metabolic alkalosis were milk-alkali syndrome, which accompanies hypercalcemia ( 4 ). However, we excluded these disorders due to the lack of hypercalcemia in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Other differential diagnoses of renal failure and metabolic alkalosis were milk-alkali syndrome, which accompanies hypercalcemia ( 4 ). However, we excluded these disorders due to the lack of hypercalcemia in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Over-the-counter self-medication can pose an additional risk in managing intoxications [ 66 ] and the risk of toxicity should be included in the safety labels for bismuth subsalicylate products, especially regarding patients with previous renal conditions [ 67 ]. In addition, it was reported that therapies including the combined intake of multiple daily doses of milk and cream combined with bismuth subcarbonate—intending to alleviate gastric ulcer symptoms—resulted in hypercalcemia, metabolic alkalosis, and cases of acute kidney injury (Milk-alkali syndrome) [ 76 ]; a potential association with over-the-counter calcium supplements for osteoporosis to this syndrome was also recently reviewed [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when calcium consumption exceeds 10 to 15 mg a day, suppressed calcitriol does not prevent the absorption of an excessive amount of calcium [ 9 ] but eventually leads to hypercalcemia, which causes further pathophysiologic changes underlying milk-alkali syndrome. The key event of the condition is calcium-induced diuresis, which stimulates renal bicarbonate absorption, leading to volume depletion and alkalosis in the setting of increased absorbable alkali intake [ 10 ]. Mechanisms underlying these events include calcium-induced vasoconstriction reducing the glomerular filtration rate; activation of calcium-sensing receptors located in medullary thick ascending limb, which leads to natriuresis via inhibition of the sodium-potassium-calcium transporter; and suppression of antidiuretic hormone-mediated free water absorption in the collecting duct [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The key event of the condition is calcium-induced diuresis, which stimulates renal bicarbonate absorption, leading to volume depletion and alkalosis in the setting of increased absorbable alkali intake [ 10 ]. Mechanisms underlying these events include calcium-induced vasoconstriction reducing the glomerular filtration rate; activation of calcium-sensing receptors located in medullary thick ascending limb, which leads to natriuresis via inhibition of the sodium-potassium-calcium transporter; and suppression of antidiuretic hormone-mediated free water absorption in the collecting duct [ 10 ]. Alkalemia further contributes to increased calcium absorption via a pH-sensitive calcium channel called the transient receptor potential vanilloid member 5 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%